2011
DOI: 10.1111/j.1468-2419.2011.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Employees' perceptions of the opportunities to utilize their competences: exploring the role of perceived competence mobilization

Abstract: Perceived competence mobilization is the degree to which employees perceive that they have adequate opportunities to utilize their competences in their current jobs. The findings of the research reported here suggest that employees' perceived competence mobilization is associated with a number of favourable employee attitudes, including intrinsic motivation, organizational commitment and intention to stay with the organization. Findings based on cross-sectional data from 881 public workers indicate that percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
(52 reference statements)
2
27
0
1
Order By: Relevance
“…In addition, we have demonstrated that developing of organizational learning process may provide the company with customer knowledge and development solutions and offer new products and services through Internet (Langerak et al, 2007;Bulut & Culha, 2010;Martin et al, 2011;Pham et al, 2013). Furthermore, the ability to innovate effectively in the context of new technology-based services depends on the extent of employees' involvement (Lai, 2011). Managers can give employees the possibility of innovating, since they are recruited to the firm, motivating innovative culture in the company (Straub, 1994;Hopeniene et al, 2009;Sooraksa, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we have demonstrated that developing of organizational learning process may provide the company with customer knowledge and development solutions and offer new products and services through Internet (Langerak et al, 2007;Bulut & Culha, 2010;Martin et al, 2011;Pham et al, 2013). Furthermore, the ability to innovate effectively in the context of new technology-based services depends on the extent of employees' involvement (Lai, 2011). Managers can give employees the possibility of innovating, since they are recruited to the firm, motivating innovative culture in the company (Straub, 1994;Hopeniene et al, 2009;Sooraksa, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…This concept is concerned with subordinates’ judgment of the relevancy of their work tasks, including the types and breadths of tasks and established goals, in utilizing their competence. Different from self‐efficacy, which refers to individual feelings of being competent, individuals experience their competence mobilized when they see opportunities for using their skills at work (Lai, ; Lai & Kapstad, ). As such, it is not deterministic in terms of the specific types and breadths of tasks but instead about employee perceptions of work and the extent to which it “fits” with their competence.…”
Section: Congruence In Leader‐subordinate Autonomy Expectations and Pmentioning
confidence: 99%
“…Indeed, a study by Lai and Kapstad () demonstrated that self‐efficacy was not related to perceived competence mobilization, arguing that the relationship can be complex depending on the extent to which the highly efficacious individuals are enthusiastic about the opportunities. This line of inquiry has gained increasing attention because how subordinates perceive competence mobilization is an important predictor of their subsequent attitudinal (e.g., Lai & Kapstad, ; Parker, ) and behavioral (e.g., Berg, Grant et al., 2010; Lai, ) responses. This is also in line with person‐job fit research, which supports the idea that the factors for individuals to thrive at work are not universal but dependent on the extent to which individuals find those factors fitting (Edwards, ; Kristof‐Brown, Zimmerman, & Johnson, ).…”
Section: Congruence In Leader‐subordinate Autonomy Expectations and Pmentioning
confidence: 99%
“…The TU creates more opportunities for COI to leverage their effects on external knowledge acquisition. First, TU creates new opportunities, new challenging responsibility for top managers to achieve intrinsic desire (Lai and Kapstad, ; Lai, ).When technological turbulence is high, it is more likely for top managers to identify and grasp the technology opportunities created by the fast changes of technologies (Calantone et al ., ; Lai and Kapstad, ; Lai, ). Therefore, external learning offers valuable opportunities for career‐oriented managers to establish achievement by exploring new ways for their organisations.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Second, high TU can strengthen the effects of COI by intensifying the managers' organisational identity (Lai and Kapstad, ; Lai, ). COI links the managers' career development and firms' growth together and thus motivate mangers to invest external knowledge acquisition.…”
Section: Hypothesis Developmentmentioning
confidence: 99%